Occludin stalls HCV particle dynamics apart from hepatocyte tight junctions, promoting virion internalization. Issue 4 (10th June 2022) - Deffieu, Maika S.; Clément, Camille M. H; Dorobantu, Cristina M.; Partiot, Emma; Bare, Yonis; Faklaris, Orestis; Rivière, Benjamin; Ayala‐Nunez, Nilda Vanesa; Baumert, Thomas F.; Rondé, Philippe; Mély, Yves; Lucansky, Vincent; et al.
Abstract: Background and Aims: Numerous HCV entry factors have been identified, and yet information regarding their spatiotemporal dynamics is still limited. Specifically, one of the main entry factors of HCV is occludin (OCLN), a protein clustered at tight junctions (TJs), away from the HCV landing site. Thus, whether HCV particles slide toward TJs or, conversely, OCLN is recruited away from TJs remain debated. Approach and Results: Here, we generated CRISPR/CRISPR‐associated protein 9 edited Huh7.5.1 cells expressing endogenous levels of enhanced green fluorescent protein/OCLN and showed that incoming HCV particles recruit OCLN outside TJs, independently of claudin 1 (CLDN1) expression, another important HCV entry factor located at TJs. Using ex vivo organotypic culture of hepatic slices obtained from human liver explants, a physiologically relevant model that preserves the overall tissue architecture, we confirmed that HCV associates with OCLN away from TJs. Furthermore, we showed, by live cell imaging, that increased OCLN recruitment beneath HCV particles correlated with lower HCV motility. To decipher the mechanism underlying virus slow‐down upon OCLN recruitment, we performed CRISPR knockout (KO) of CLDN1, an HCV entry factor proposed to act upstream of OCLN. Although CLDN1 KO potently inhibits HCV infection, OCLN kept accumulating underneath the particle, indicating that OCLN recruitment is CLDN1 independent. Moreover, inhibition of the phosphorylation of Ezrin, a protein involved in HCV entry that links receptors to the actin cytoskeleton, increased OCLN accumulation and correlated with more efficient HCV internalization. Conclusions: Together, our data provide robust evidence that HCV particles interact with OCLN away from TJs and shed mechanistic insights regarding the manipulation of transmembrane receptor localization by extracellular virus particles. Abstract :